Preliminary physico-chemical and microbial analyses of bottled water sold in the University of the Philippines Los Baños. - Barrion, A. S. A.; Rabaja, H. M. M.; Hurtada, W. A. (2003)
The public's demand for safe drinking water enabled the bottled water industry to flourish in the recent years. Within the industry's growth came concerns on ensuring proper procedures in maintaining the cleanliness of containers, sealing, transporting, and storing these bottled water products to prevent or minimize the risk of contamination. Thus, it is extremely important to monitor regularly the quality standards of these bottled waters sold to the public. Physical, chemical, and microbial analyses were conducted to determine the quality of four brands with improperly labeled bottled drinking water sold in the University of the Philippines Los Baños campus. The results indicate that all samples met the physical color and turbidity) and chemical (total dissolved solids and pH) standards of both the World Health organization (WHO) and the Philippine national standards for drinking water however, in terms of microbial safety, all four samples failed to meet both the WHO and national safety standards. The samples were positive for total and fecal coliform. The potability test showed that samples had >8.0 MPN/100 ml numbers of total and fecal coliforms. To improve safety standards on bottled drinking water, there is a need to establish and implement a strict code of practice in the processing of bottled water products. Local authorities, vendors, and consumers should also take note of proper product labelling rules.
Keywords: University of the Philippines (Los Baños); Bottled water; Drinking water; Contamination of drinking water